Dose-response and isotemporal substitution analysis of domain-specific physical activity and sedentary behavior with abdominal aortic calcification risk: A cross-sectional study - Zhuohui Yang; Lin Zhu; Zekai Chen (PLoS ONE, 2025)
Background Abdominal aortic calcification (AAC) is an independent risk factor for cardiovascular disease. This study aims to examine the dose-response relationships between domain-specific moderate-to-vigorous physical activity (MVPA), sedentary behavior (SB), and AAC risk, and the effects of time reallocation among these behaviors, in individuals aged 40 years and older. Methods This cross-sectional study used data from NHANES participants from the 2013–2014 cycle. MVPA and SB were self-reported, and AAC status was assessed using the Kauppila scoring system and DXA. Weighted logistic regression calculated odds ratio (OR) and 95% confidence interval (CI) for dose-response relationships, using restricted cubic splines (RCS). Furthermore, weighted logistic regression models within an isotemporal substitution analysis were employed to examine the effect on AAC risk of reallocating time among different MVPA domains and sedentary behavior. Results This study included 2,842 participants (median age 58 years, interquartile range [IQR] 48−68 years, 48.42% male), of whom 861 (30.30%) had AAC. Adherence to physical activity (PA) guidelines (≥150 minutes/week) for leisure-time MVPA was associated with a 33.7% reduction in AAC risk (OR = 0.643, 95% CI 0.488–0.848, P = 0.035). However, no significant effect of occupation and transportation-related MVPA on reducing AAC risk was found. RCS revealed dose-response relationships between total MVPA, leisure-time MVPA, and SB with AAC risk, indicating a U-shaped pattern for total MVPA, with the lowest risk at 1086 minutes/week (OR = 0.712, 95% CI 0.546–0.928, non-linear P = 0.023). Moreover, isotemporal substitution analysis showed that replacing 30 minutes/day of sedentary behavior (OR: 0.837, 95% CI: 0.747–0.927) or occupational MVPA (OR: 0.842, 95% CI: 0.692–0.992) with leisure-time MVPA was significantly associated with lower AAC risk. Conclusion There is a positive linear dose-response association between sedentary behavior and AAC risk; conversely, leisure-time MVPA shows a negative linear dose-response association. Total MVPA presents a nonlinear dose-response association, with AAC risk being lowest when activity reaches 1086 minutes per week. Isotemporal substitution analysis further revealed that reallocating time from sedentary behavior or occupational MVPA to leisure-time MVPA is associated with a lower risk of AAC. These results suggest that increasing leisure-time MVPA and reducing sedentary behavior may help optimize AAC risk.